‘Samisk religion’ i skolen: En kvalitativ analyse av et utvalg lærere sin religionsundervisning om ‘samisk religion’ - Vågane, Susanne Solsvik (The University of Bergen, 2024)
In August 2020, a new curriculum was introduced in Kristendom, religion, livssyn og etikk (KRLE), and Religion og etikk. It was a renewal of Læreplanverket for Kunnskapsløftet, which resulted in numerous alterations. One of the changes was the explicit acknowledgment of Sámi peoples as indigenous peoples. Another alteration was that every Norwegian student is now supposed to acquire broad knowledge about Sámi peoples, which includes history, culture, society, and legal rights. The purpose of this study is to gain insight into how teachers experience teaching about ‘Sámi religion’, and some of the challenges that may occur in the classroom. This study examines the experiences of eight teachers teaching about ‘Sámi religion’ to secondary and upper-secondary students around the area of Bergen, Norway. The interviews show that they have different interpretations of the competence aims and the more general parts of the curriculum. This results in different teaching practices when it comes to ‘Sámi religion’, with teachers setting aside varying lengths of time for the subject as well as emphasizing different topics within the religion. This diversity in teaching approaches in an educational setting reflects factors such as interests, teacher education, feelings of uncertainty, and differing individual competencies. Furthermore, it becomes clear from the interviews that certain didactic challenges occur in the process, including e.g. essentialism, exoticization, othering, and the authority of knowledge in relation to textbooks. Religionsvitenskap mastergradsoppgave RELV350 MAHF-RELV MAHF-LÆHR